Activated M2 Macrophages Contribute to the Pathogenesis of IgG4‐Related Disease via Toll‐like Receptor 7/Interleukin‐33 Signaling. Issue 1 (29th November 2019) - Ishiguro, Noriko; Moriyama, Masafumi; Furusho, Katsuhiro; Furukawa, Sachiko; Shibata, Takuma; Murakami, Yusuke; Chinju, Akira; Haque, A. S. M. Rafiul; Gion, Yuka; Ohta, Miho; Maehara, Takashi; Tanaka, Akihiko; et al.
Abstract : Objective: IgG4‐related disease (IgG4‐RD) is a unique inflammatory disorder in which Th2 cytokines promote IgG4 production. In addition, recent studies have implicated the Toll‐like receptor (TLR) pathway. This study was undertaken to examine the expression of TLRs in salivary glands (SGs) from patients with IgG4‐RD. Methods: SGs from 15 patients with IgG4‐RD, 15 patients with Sjögren's syndrome (SS), 10 patients with chronic sialadenitis, and 10 healthy controls were examined histologically. TLR family gene expression (TLR‐1 through TLR‐10) was analyzed by DNA microarray in the submandibular glands (SMGs). Up‐regulation of TLRs was confirmed in SGs from patients with IgG4‐RD. Finally, the phenotype of human TLR‐7 (huTLR‐7)–transgenic C57BL/6 mice was assessed before and after stimulation with TLR agonist. Results: In patients with IgG4‐RD, TLR‐4, TLR‐7, TLR‐8, and TLR‐9 were overexpressed. Polymerase chain reaction validated the up‐regulation of TLR‐7 in IgG4‐RD compared with the other groups. Immunohistochemical analysis confirmed strong infiltration of TLR‐7–positive cells in the SGs of patients with IgG4‐RD. Double immunohistochemical staining showed that TLR‐7 expression colocalized with CD163+ M2 macrophages. After in vitro stimulation with a TLR‐7 agonist, CD163+ M2 macrophages produced higher levels of interleukin‐33 (IL‐33), which is a Th2‐activating cytokine. In huTLR‐7–transgenic mice, the focus and fibrosis scores in SMGs, pancreas, and lungs were significantly higher than those in wild‐type mice ( P < 0.05). Moreover, the concentration of serum IgG, IgG1, and IL‐33 in huTLR‐7–transgenic mice was distinctly increased upon stimulation with a TLR‐7 agonist ( P < 0.05). Conclusion: TLR‐7–expressing M2 macrophages may promote the activation of Th2 immune responses via IL‐33 secretion in IgG4‐RD.